Lycoperoside H, a Tomato Seed Saponin, Improves Epidermal Dehydration by Increasing Ceramide in the Stratum Corneum and Steroidal Anti-Inflammatory Effect - Takeda, Shogo; Miyasaka, Kenchi; Shrestha, Sarita; Manse, Yoshiaki; Morikawa, Toshio; Shimoda, Hiroshi (Molecules (Basel, Switzerland), 2021)
Tomatoes are widely consumed, however, studies on tomato seeds are limited. In this study, we isolated 11 compounds including saponins and flavonol glycosides from tomato seeds and evaluated their effects on epidermal hydration. Among the isolated compounds, tomato seed saponins (10 µM) significantly increased the mRNA expression of proteins related to epidermal hydration, including filaggrin, involucrin, and enzymes for ceramide synthesis, by 1.32- to 1.91-fold compared with the control in HaCaT cells. Tomato seed saponins (10 µM) also decreased transepidermal water loss by 7 to 13 g/m2·h in the reconstructed human epidermal keratinization (RHEK) models. Quantitative analysis of the ceramide content in the stratum corneum (SC) revealed that lycoperoside H (1–10 µM) is a promising candidate to stimulate ceramide synthesis via the upregulation of ceramide synthase-3, glucosylceramide synthase, and β-glucocerebrosidase, which led to an increase in the total SC ceramides (approximately 1.5-fold) in concert with ceramide (NP) (approximately 2-fold) in the RHEK models. Evaluation of the anti-inflammatory and anti-allergic effects of lycoperoside H demonstrated that lycoperoside H is suggested to act as a partial agonist of the glucocorticoid receptor and exhibits anti-inflammatory effects (10 mg/kg in animal test). These findings indicate that lycoperoside H can improve epidermal dehydration and suppress inflammation by increasing SC ceramide and steroidal anti-inflammatory activity.